Directing. - Kozelka, Paul. (New York: Richards Rosen Press, 1968)
Discusses various aspects of directing including selecting and analyzing a play, conducting tryouts, and setting up rehearsal schedules.
Bibliography: p. 173-184.
Keywords: Artet boterore; Arti skenik-teatri-drama; Aktrimi-interpretimi; Theater -- Production and direction.-prodhimi dhe drejtimi; Theater -- Teoria e artit skenik; Teoria e drames; Teatri-drama-organizimi-realizimi-provat